2001
DOI: 10.1007/s004640090050
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical outcomes after subfascial endoscopic perforator surgery (SEPS) and saphenous vein surgery in chronic venous insufficiency

Abstract: SEPS is safe and feasible. Early clinical results have shown a promising outcome in patients with severe chronic venous insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…After excluding duplicate reports, 18 articles had data on healing outcomes after SEPS. [6][7][8][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Two studies found in references of included studies were added, 28,29 for a total of 20 included studies. Of these, 19 were case series and 1 was a randomized trial that compared open perforator ligation with SEPS.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicate reports, 18 articles had data on healing outcomes after SEPS. [6][7][8][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Two studies found in references of included studies were added, 28,29 for a total of 20 included studies. Of these, 19 were case series and 1 was a randomized trial that compared open perforator ligation with SEPS.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical severity and disability scores as proposed by the American Venous Forum Executive Committee were registered before and after surgery. 10,11 Continuous data were compared by using the t test or the Mann-Whitney test, where appropriate, and the 2 test was used for the comparison of proportions. Survival analyses were performed according to the method described by Kaplan and Meier.…”
Section: Methodsmentioning
confidence: 99%
“…Rare applications of the harmonic scalpel in laparoscopic surgery, only performed by individual surgeons largely experienced in the technique, include gastric resections [21], laparoscopic cholecystectomy [22,24,44], liver resections [18,20,34,42,47], pancreatic surgery (management of pseudocysts) [45,52] or subfascial endoscopic perforator surgery (SEPS) for treatment of chronic venous insufficiency [33] and resection of large connective tissue tumors [37,38,41]. The use of the harmonic scalpel for breast surgery has been reported by single groups [8,9,16].…”
Section: Application Of the Harmonic Scalpel In General Surgerymentioning
confidence: 99%
“…Besides its impact on gynaecologic [30], urologic [23,50], otolaryngeal [51] and vascular surgery [33], it has now gained broad acceptance for general surgery. From a theoretical point of view, high-frequency ultrasound-based technology for tissue dissection and vessel sealing is suggested to facilitate surgical procedures.…”
Section: Introductionmentioning
confidence: 99%